THE ROLE OF AUDIO, VIDEO AND COMPUTER-MEDIATED COMMUNICATION IN LANGUAGE LEARNING - Xoliqulova Hulkaroy; Samadova Visola (TADQIQOTLAR, 2026)
Annotation.  This  article  examines  the  role  of  audio,  video,  and  computer-mediated communication (CMC) in language learning. It explains how these tools help learners  develop  listening,  speaking,  reading,  and  writing  skills.  The  article  also highlights  the  advantages  and  disadvantages  of  each  method  and  emphasizes  the importance  of  using  them  together.  Special  attention  is  given  to  modern  digital technologies and communication platforms. The study concludes that the integration of  audio,  video,  and  CMC  tools  leads  to  more  effective  and  interactive  language learning.